Kontrol Mouse Menggunakan Webcam Berdasarkan Deteksi Warna - Feri Fadli Aiyub; Munawir Munawir (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
The interaction technology in general is inseparable from the rapid development of Human-Computer Interaction technology or Human and Computer Interaction. Human and computer mouse interactions are called Virtual Mouse. Virtual mouse is designed for users to be able to interact directly with computers without using input devices such as conventional mice but using their hands as driving objects or using other media such as colors. In this research, testing is done on how to track an object that moves in order to do the mouse by using an intermediary in the form of an image processing-based webcam video that is taken in real-time using object tracking in the form of three color variables arranged based on RGB composition using the optical flow method in detecting its movement. Based on research that has been carried out as a whole the color object used as a pointer controller or mouse with the optical flow method can be detected properly in every condition.